Efektifitas Model Pembelajaran Kooperatif Tipe Coop-Coop dalam Peningkatan Hasil Belajar Ekonomi di Kelas XI MA Palapa Nusantara: The Effectiveness of the Coop-Coop Type Cooperative Learning Model in Improving Student Learning Outcomes in the Economics Subject of Class XI MA Palapa Nusantara - M. Saipul Watoni (Pendidikan Al-Gafari, 2025)
Education plays a crucial role in creating an intelligent, peaceful, open, and democratic life. Therefore, educational reform must be continuously implemented to improve the quality of national education. This study aims to determine the effectiveness of the cooperative learning model of the coop-coop type on the learning outcomes of Economics of class XI students of MA Palapa Nusantara. This study is an experimental study involving 72 students of class XI1 and XI2 of MA Palapa Nusantara who were determined by random sampling technique, namely class XI1 as the experimental class and class XI2 as the control class. The research design used is